Изучение поли(U) - и поли(dT)-зависимого связывания Phe-tРНКᴾʰᵉ с 30S субчастицами рибосом Escherichia coli - Солдаткин, К.А.; Потапов, А.П.; Солдаткин, А.П.; Ельская, А.В. (Биополимеры и клетка, 1987)
Показано, что в условиях бесфакторного связывания Phе-тРНКᴾʰᵉ с 30S субчастицами Е. coli матричная активность поли(U) заметно выше, чем поли(dТ). Наличие или отсутствие 2'-ОН-групп кодонов существенно для связывания субстрата в А-центре. Влияние неомицина на связывание Phe-тPHKᴾʰᵉ с малой субчастицей относительно слабое. По-видимому, высокая чувствительность трансляции к антибиотику скорее определяется этапом транслокации. Показано, що в умовах безфакторного зв’язування Phе-тРНКᴾʰᵉ з 30S субчастинками Е. coli матрична активність полі(U) помітно вища, ніж полі(dТ). Наявність чи відсутність 2'-ОН-груп кодонів є суттєвою для зв’язування субстрату в А-центрі. Вплив неоміцину на зв’язування Phe-тPHKᴾʰᵉ з малою субчастинкою відносно слабкий. Ймовірно, висока чутливість трансляції до антибіотика швидше визначається етапом транслокації. To study the role of the codon sugar-phosphate backbones in the mRNA decoding process we have compared the messenger activity of authentic ribo- and deoxyribopolynucle-otides, poly(U) and poly(dT), in the factor-free binding of Phe-tRNAᴾʰᵉ to the SOS subunits of E. coli ribosomes. The template efficiency of poly(U) is much higher than that of poly(dT). Template 2'-hydroxyl groups seem to be important for the binding process at the A site of SOS subunit. The results obtained indicate the co-operative nature of the occupation of the P and A sites of SOS subunits. Neomycin exerted an insignificant effect upon the Phe-tRNAᴾʰᵉ binding. High sensitivity of translation efficiency to neomycin may be due to the translocation stage.